A PERFORMANCE ANALYSIS OF PRODUCTION UNITS FOLLOWING THEIR REINTRODUCTION IN SELECTED SECONDARY SCHOOLS OF LUSAKA (Isagoge - Journal of Humanities and Social Sciences, 2022)
Production units were a common feature in most schools during the United Independence Party (UNIP) Government. They were an important component of preparing learners for independent living as well as a way of making schools a second home for learners where learners could learn and eat. This study assessed the performance of Production Units in selected secondary schools in Lusaka District. The objectives of the study were; to establish how the Production Units were managed in selected schools in Lusaka District and to explore the challenges that were affecting the performance of Production Units in schools. A qualitative research approach and a descriptive design were adopted. Eighteen (18) participants in charge production units in the three selected schools were purposively selected and involved in the study. The composition of sample was Three (03) Head- teachers; Three (03) Heads of Departments; and Six (06) Science Teachers; and Six (06) General Workers, all members that were purposively selected by virtue of their involvement in production unit. The findings established that that schools had established structures that guided the management of production units. It was further established that decisions were made democratically on how production units should run in each school sampled in the study. In terms of the performance, it was revealed that the units were adding value to schools through the activities undertaken under production units. Some challenges were identified in terms of how the production units were operating in schools. These included: shortage of land, poor planning in terms of timing of activities to do with production units, lack of proper training, lack of transport and market, and inadequate financial resources for expanding production units’ activities. Arising from the findings of the study, the following recommendations were made: workers under production units should be trained; schools to develop marketing strategies through working with supermarkets, hotels and lodges. Also, land to be secured through the help of Ministry of General Education and Ministry of Lands for schools to expand their ventures.
Keywords: Assessment, Challenges, School, Performance, Production Units